2020
DOI: 10.3389/fmicb.2020.00238
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Green Synthesis and Characterization of Silver Nanoparticles Using Melia azedarach for the Management of Fusarium Wilt in Tomato

Abstract: Managing Fusarium Wilt Through Nanoparticles the field of plant pathology by introducing an environment-friendly approach for disease management and playing a potential part in agriculture industry. However, to date, little work has been done to integrate nanotechnology into phytopathology so, this area of research is in need of adoption and exploration for the management of plant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 99 publications
4
36
0
Order By: Relevance
“…The results of the present study showed that AgNPs have antibacterial and antifungal activity in vitro against R. solanacearum and F. oxysporum, respectively. This finding is consistent with previous studies, which showed that AgNPs are effective for killing phytopathogens (including fungi, Gram-positive bacteria, and Gram-negative bacteria) ( Table 1 ) [ 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Not all of them have carried out a basic characterization of the biogenic AgNPs obtained, which makes it difficult to explain the mechanism by which AgNPs interact with these microorganisms.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study showed that AgNPs have antibacterial and antifungal activity in vitro against R. solanacearum and F. oxysporum, respectively. This finding is consistent with previous studies, which showed that AgNPs are effective for killing phytopathogens (including fungi, Gram-positive bacteria, and Gram-negative bacteria) ( Table 1 ) [ 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Not all of them have carried out a basic characterization of the biogenic AgNPs obtained, which makes it difficult to explain the mechanism by which AgNPs interact with these microorganisms.…”
Section: Resultssupporting
confidence: 93%
“…Until now, only a few articles including (at the same publication) results of antinematode, antifungal, and antibacterial studies against plant pathogens using AgNPs have been reported [ 23 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Therefore, in this work, we screened the biosynthesized AgNPs against the plant pathogenic bacterium, R. solanacearum, and fungus, F. oxysporum .…”
Section: Resultsmentioning
confidence: 99%
“…64 The microwave was used successfully for the development of different formulations. [65][66][67] 3.6. Characterization of M. viridis polymeric micelles and their anti-Helicobacter potential…”
Section: Preparation Of M Viridis Polymeric Micellesmentioning
confidence: 99%
“…UV-Vis spectrophotometer was used to first confirm synthesis and presence of nanoparticles in the reaction mixture. Earlier literature showed that absorption between 400 -450 nm is usually characteristic of silver NPs in the UV-Vis region (Sathishkumar et al 2009;Ashraf et al 2020). Clear peaks recorded at 413 and 410 nm in case of reaction mixture containing extracts of white mulberry and bael leaves thus followed the trend.…”
Section: Discussionmentioning
confidence: 63%